Intra thyroid thyroglossal cyst: a rare presentation - P., Lakshmi V.; Surendran, Divya; Moothiringode, Savithri (International Journal of Research in Medical Sciences, 2019)
Thyroglossal duct cyst is a congenital malformation occurring due to incomplete closure of the thyroglossal duct. The infrequency with which it is encountered in thyroid makes it a formidable diagnostic challenge. Authors report this case because of the rarity of intrathyroid location of thyroglossal cyst.